2010
DOI: 10.4103/0973-8398.76738
|View full text |Cite
|
Sign up to set email alerts
|

Interpenetrating polymeric network hydrogel for stomach-specific drug delivery of clarithromycin: Preparation and evaluation

Abstract: T he aim of this study was to develop a controlled release system targeting antibiotic delivery to the stomach. The hydrogels were synthesized by using chitosan, poly (acrylic acid) and poly (vinyl pyrrolidone) polymers crosslinked with glutaraldehyde and N,N'-methylenebisacrylamide. Interpenetrating polymeric network (IPN) hydrogels were prepared by varying the concentration of crosslinking agent (glutaraldehyde). The amount of chitosan, poly (acrylic acid), poly (vinyl pyrrolidone) and N,N'-methylenebisacryl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 11 publications
(13 reference statements)
0
6
0
Order By: Relevance
“…They observed that these covalently cross-linked hydrogels were pH sensitive and showed maximum swelling and drug release at low pH in the stomach environment owing to protonation of an amino group achieving the targeted sustained release. The purpose of introducing acrylic acid as graft is to control the swelling (to avoid burst release) and to achieve sustained release of the antibiotic [ 125 ].…”
Section: Applications Of Ph Sensitive Hydrogelsmentioning
confidence: 99%
“…They observed that these covalently cross-linked hydrogels were pH sensitive and showed maximum swelling and drug release at low pH in the stomach environment owing to protonation of an amino group achieving the targeted sustained release. The purpose of introducing acrylic acid as graft is to control the swelling (to avoid burst release) and to achieve sustained release of the antibiotic [ 125 ].…”
Section: Applications Of Ph Sensitive Hydrogelsmentioning
confidence: 99%
“…The mucoadhesive property of a material is generally carried out by two methods: wash-off method and tensile method [187] . The wash-off method involves adhesion of the samples over the excised mucosal lining (attached over a glass slide).…”
Section: Mucoadhesivitymentioning
confidence: 99%
“…Many examples of drug delivery applications using acrylic acid copolymerized with other monomers in natural polymers have been published recently. Gupta et al prepared pH-sensitive hydrogels for the stomach-targeted drug delivery of clarithromycin [ 26 ]. Acrylic acid was used to graft chitosan by free radical polymerization, blended with poly(vinyl pyrrolidone), and crosslinked with glutaraldehyde and N , N -methylenebisacrylamide.…”
Section: Introductionmentioning
confidence: 99%